Oscillatory mTOR inhibition and Treg increase in kidney transplantation. (28th August 2015) - Sabbatini, M.; Ruggiero, G.; Palatucci, A. T.; Rubino, V.; Federico, S.; Giovazzino, A.; Apicella, L.; Santopaolo, M.; Matarese, G.; Galgani, M.; Terrazzano, G.
Summary Intracellular metabolic pathways dependent upon the mammalian target of rapamycin (mTOR) play a key role in immune‐tolerance control. In this study, we focused on long‐term mTOR‐dependent immune‐modulating effects in kidney transplant recipients undergoing conversion from calcineurin inhibitors (CNI) to mTOR inhibitors (everolimus) in a 1‐year follow‐up. The conversion to everolimus is associated with a decrease of neutrophils and of CD8+ T cells. In addition, we observed a reduced production of interferon (IFN)‐γ by CD8+ T cells and of interleukin (IL)‐17 by CD4+ T lymphocytes. An increase in CD4+CD25+ forkhead box protein 3 (FoxP3)+ [regulatory T cell [(Treg)] numbers was also seen. Treg increase correlated with a higher proliferation rate of this regulatory subpopulation when compared with the CD4+FoxP3− effector counterpart. Basal phosphorylation level of S6 kinase, a major mTOR‐dependent molecular target, was substantially maintained in patients treated with everolimus. Moreover, oscillations in serum concentration of everolimus were associated with changes in basal and activation‐dependent S6 kinase phosphorylation of CD4+ and CD8+ T cells. Indeed, T cell receptor (TCR) triggering was observed to induce significantly higher S6 kinase phosphorylation in the presence of lower everolimus serum concentrations. These results unveil the complex mTOR‐dependent immune‐metabolic network leading to long‐term immune‐modulation and might have relevance for novel therapeutic settings in kidney transplants.